2016
DOI: 10.1021/acsami.5b11671
|View full text |Cite
|
Sign up to set email alerts
|

Nanotopography-Induced Structural Anisotropy and Sarcomere Development in Human Cardiomyocytes Derived from Induced Pluripotent Stem Cells

Abstract: Understanding the phenotypic development of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) is a prerequisite to advancing regenerative cardiac therapy, disease modeling, and drug screening applications. Lack of consistent hiPSC-CM in vitro data can be largely attributed to the inability of conventional culture methods to mimic the structural, biochemical, and mechanical aspects of the myocardial niche accurately. Here, we present a nanogrid culture array comprised of nanogrooved topogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(191 citation statements)
references
References 62 publications
6
185
0
Order By: Relevance
“…One example of an attempt to mimic the native myocardial niche in vitro is the utilization of biomimetic nano-structured surfaces to improve cell adhesion, proliferation, and migration, as well as cardiomyogenic differentiation and structural development (Carson et al, 2016, Kim, Kshitiz, 2012a). Parallel nano-grooves and nano-ridges help maintain the cell polarity and alignment important for organ development by providing contact guidance which influences the organization of microtubules, focal contacts, and actin filaments in parallel with the underlying topography (Kim et al, 2012b).…”
Section: Biomimetic Strategies For Human Cardiac Tissue Engineeringmentioning
confidence: 99%
“…One example of an attempt to mimic the native myocardial niche in vitro is the utilization of biomimetic nano-structured surfaces to improve cell adhesion, proliferation, and migration, as well as cardiomyogenic differentiation and structural development (Carson et al, 2016, Kim, Kshitiz, 2012a). Parallel nano-grooves and nano-ridges help maintain the cell polarity and alignment important for organ development by providing contact guidance which influences the organization of microtubules, focal contacts, and actin filaments in parallel with the underlying topography (Kim et al, 2012b).…”
Section: Biomimetic Strategies For Human Cardiac Tissue Engineeringmentioning
confidence: 99%
“…In addition, nanopatterned substrates have been widely used to encourage maturation of chemically defined CMs 7376 . However, new methods proposed thus far have not yielded highly mature, patient-specific CMs on a scale sufficient to meet clinical needs 77 .…”
Section: Cell Therapy For Salvage and Regeneration Of Heart Tissuementioning
confidence: 99%
“…Such substrates enable control of neuritic outgrowth and polarity, which may also offer benefits when seeking to develop controlled neuronal networks [Ferrari et al, 2011]. Studies into other electrically active cell types, like cardiomyocytes, have demonstrated that topographic patterning can enhance physiological structure and function [Yang et al, 2014a;Carson et al, 2016] but whether or not such surfaces enhance network connectivity and functional performance in iPSC-based neuronal cultures remains to be seen. Highly conductive substrates have been shown to improve network activity in cultured neuronal populations [Lovat et al, 2005;Tang et al, 2013].…”
Section: Maturitymentioning
confidence: 99%